2019
DOI: 10.18632/oncotarget.27047
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist uptake of comprehensive genomic profile guided targeted therapy

Abstract: We describe the extent to which comprehensive genomic profiling (CGP) results were used by oncologists to guide targeted therapy selection in a cohort of solid tumor patients tested as part of standard care at Roswell Park Comprehensive Cancer Center June 2016–June 2017, with adequate follow up through September 2018 ( n = 620). Overall, 28.4% of CGP tests advised physicians about targeted therapy use supported by companion diagnostic or practice guideline evidence. Post-test targeted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…[9][10][11][12] Considering the time of follow-up of our study (in most of patients F1CDx was performed in the last 6 months of the study), and the fact that many patients did not progress to their ongoing therapies, probably we will reach this percentage during next years. Indeed, a good number of prospective [17][18][19][20][21][22][23] and retrospective [24][25][26][27] trials evaluated CGP using different techniques (NGS, WES, WGS) but in the context of large academic centres. Largest prospective study defined the potential and the limitations of extensive genomic panel (SHIVA, 17 NCI-MATCH, 18 NCI-MPACT, 19 ASCO-TAPUR, 20 I-PREDICT, 21 WINTHER, 22 PROFILER.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Considering the time of follow-up of our study (in most of patients F1CDx was performed in the last 6 months of the study), and the fact that many patients did not progress to their ongoing therapies, probably we will reach this percentage during next years. Indeed, a good number of prospective [17][18][19][20][21][22][23] and retrospective [24][25][26][27] trials evaluated CGP using different techniques (NGS, WES, WGS) but in the context of large academic centres. Largest prospective study defined the potential and the limitations of extensive genomic panel (SHIVA, 17 NCI-MATCH, 18 NCI-MPACT, 19 ASCO-TAPUR, 20 I-PREDICT, 21 WINTHER, 22 PROFILER.…”
Section: Discussionmentioning
confidence: 99%
“…Despite guidelines, the uptake of CGP in the community has not been uniform, even in NSCLC patients and the general impact of CGP as to patient outcomes and cost effectiveness remains unclear [13,14]. A large retrospective study of advanced NSCLC patients treated in the community setting identified gaps in national guideline based genomic testing for EGFR and ALK [4].…”
Section: Introductionmentioning
confidence: 99%
“… Ability of both clinicians and molecular pathologists to be/keep up to date with the rapidly changing treatment landscape . Interpreting molecular results will require the expertise of molecular pathologists and geneticists [ 64 ]. While molecular tumor boards [ 65 ] are becoming more established in the Western world, they remain an uncommon phenomenon in emerging countries.…”
Section: Recommendations For Adopting Precision Oncology In Mcrpcmentioning
confidence: 99%